Bamboo charcoal/phase change material/stainless steel ring-spun complex yarn and its far-infrared/anion-releasing elastic warp-knitted fabric: Fabrication and functional evaluation. (August 2016) - Lin, Jia-Horng; Huang, Yu-Tien; Li, Ting-Ting; Lin, Chin-Mei; Lou, Ching-Wen
In this study, far-infrared/anion-releasing elastic warp-knitted fabrics were successfully fabricated. Firstly, the composition and twist degree of ring-spun complex yarns that were made by rotor-twisting machine and ring-spinning frame were optimized based on twist contraction, hairiness, and tenacity measurements. The shell materials—1-ply bamboo charcoal (BC) roving, 1-ply phase change material (PCM) or the both (BC/PCM), and the core material—BC/stainless steel (BC/SS) wrap yarn, were formed into different compositions of ring-spun complex yarns. Afterward, elastic warp-knitted fabrics were fabricated using the optimized complex yarns as weft yarns, and rubber threads and polyester (PET) filaments as warp yarns. Air permeability, far-infrared emissivity, and anion amount of resulting warp-knitted fabrics were evaluated. Ring-spun complex yarn result shows that, twist contraction rate ratio increased, but hairiness decreased with increase of twist degree. Tenacity of ring-spun complex yarn made by BC roving (Type A) or PCM roving (Type B) first increased and then decreased with twist degree. However, when 1-ply BC and 1-ply PCM rovings were used as shell materials, the tenacity of resulting ring-spun complex yarn (Type C) decreased with twist degrees. Consequently, 12 twists per inch (T.P.I.) was the optimal twist degree for the following fabrication of warp-knitted fabrics. Air permeability, far-infrared emissivity, and anion amount of elastic warp-knitted fabrics composed of BC/SS wrap yarn and BC roving reached 44.35 cm 3 /s/cm 2, 0.94ɛ and 420 counts/cm 3, respectively, indicating excellent breathability and far-infrared/anion-releasing health care functions.